2022
DOI: 10.15376/biores.18.1.islam
|View full text |Cite
|
Sign up to set email alerts
|

Rice straw as a source of nanocellulose for sustainable food packaging materials: A Review

Abstract: Asian countries, despite being the largest producers and yielding a significant proportion of the world’s rice, have poor disposal facilities for the harvested rice straw (stubble). Due to higher costs in their handling relative to their value, local farmers prefer the burning of stubble fields, thus creating environmental problems. Even though the government has taken initiatives, no effective solution has been discovered to handle this large agro-waste problem efficiently. In this regard, the utilization of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 105 publications
(136 reference statements)
0
4
0
Order By: Relevance
“…A report stated that a decrease in the surface roughness of fiber was seen with a higher carboxylic content [ 20 ]. Recent research has demonstrated that self-fibrillation or auto-liberation of nanofibrils during sequential TEMPO/periodate oxidation is conceivable as long as the surface charge is sufficient [ 30 , 31 ].
Figure 4.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A report stated that a decrease in the surface roughness of fiber was seen with a higher carboxylic content [ 20 ]. Recent research has demonstrated that self-fibrillation or auto-liberation of nanofibrils during sequential TEMPO/periodate oxidation is conceivable as long as the surface charge is sufficient [ 30 , 31 ].
Figure 4.
…”
Section: Resultsmentioning
confidence: 99%
“…Transmission electron micrographs of cellulose showed the interlinked and large fibers with a micrometric diameter (1.6 µm), whereas the CNF was found to be well-arranged thread like network with the diameter of 15–20 nm, confirming the effective oxidation process of cellulose fibers ( Figure 5 ). Other study by Islam et al on nanocellulose extracted from rice straw exhibited average diameter of 10–50 nm [ 31 ]. Thus, nanofibers generated in the present study had lower diameter than CNF already report in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…The potential of rice straw extends beyond its role as a waste product. As a lignocellulosic biomass, it is primarily composed of 40-50% cellulose, 25-35% hemicellulose, and 15-20% lignin, presenting an opportunity for extracting valuable materials [7][8][9][10]. Cellulose is a key component in biofuel production, biodegradable materials, and high-strength composites, marking a cornerstone in the development of sustainable materials.…”
Section: Introductionmentioning
confidence: 99%
“…Cellulose is a key component in biofuel production, biodegradable materials, and high-strength composites, marking a cornerstone in the development of sustainable materials. Lignin offers potential in creating bio-based chemicals and materials, facilitating a transition towards a circular economy, where waste materials are converted into valuable resources [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Among many attractive degradable polymer materials, poly(lactic acid) (PLA), poly-β-hydroxybutyrate (PHB), polybutylene succinate (PBS), poly(butylene adipate-co-terephthalate) (PBAT), chitosan (CS), starch, and natural fibers such as crop straw are being studied to synthesize sustainable composites (Fig. 1) (Jamróz et al 2019;Mochane et al 2021;Yanat and Schroën 2021;Kumari et al 2022;Paydayesh et al 2022;Yuan et al 2023). Most biobased raw materials are biodegradable and non-toxic, which are properties that make them suitable for use in a variety of applications (Liu et al 2020;Wu et al 2022;Ren et al 2023;Setyarini et al 2023).…”
Section: Introductionmentioning
confidence: 99%